Dicarboxylic esters: Useful tools for the biocatalyzed synthesis of hybrid compounds and polymers - Bassanini, Ivan; Hult, Karl; Riva, Sergio (Beilstein Journal of Organic Chemistry, 2015)
Dicarboxylic acids and their derivatives (esters and anhydrides) have been used as acylating agents in lipase-catalyzed reactions in organic solvents. The synthetic outcomes have been dimeric or hybrid derivatives of bioactive natural compounds as well as functionalized polyesters.
Keywords: biocatalysis; dicarboxylic acids; lipase; polyesters; regioselectivity